What if We Got Rid of the Goy: Rereading Ancient Jewish Distinctions - Rozen-Tsevi, Yishai (Journal for the study of Judaism, 2016)
The goy has been present in Jewish discourses since antiquity. Despite this, its birth and history have received almost no scholarly attention. In this paper we shift the focus from the various historical attitudes towards the goy, to the very constitution of the concept and the dichotomy it constructs. We claim that scholars have been anachronistically reading Jewish (or Judaean) texts from the centuries before the common era as if they contained the Jew/goy distinction. Through a series of readings in texts like Jubilees, Pseudo-Aristeas, Joseph and Aseneth, 1-4 Maccabees, the Damascus Document, we seek to demonstrate the plurality of options for separation that existed before the Jew/goy discourse took over.